Changes in diurnal temperature range in Finland between 1961–1990 and 1991–2020 - Lohtander, Aleksi (Helsingin yliopisto, 2024)
Diurnal temperature range (DTR), defined as the difference between daily maximum and minimum temperatures, is an important variable in ecosystem dynamics. Human-induced climate change, which has increased mean temperatures worldwide, has been noted to cause global changes in DTR. In this thesis, the changes in daily maximum and minimum temperatures, as well as diurnal temperature range, were studied between the climatological periods of 1961–1990 and 1991–2020 from twenty weather observation stations in Finland. Student’s t-test was utilized to assess the statistical significance of the differences between period mean values. The results show that daily maximum and minimum temperatures have risen significantly across Finland in all seasons. The differences between 1961–1990 and 1991–2020 mean values were +1.26 °C and +1.51 °C for daily maximum and minimum temperatures, respectively. Both daily maximum and minimum temperatures have risen most notably in winter (DJF), with daily extreme temperatures increasing asymmetrically. The increase in temperatures was more pronounced for daily minimum temperatures, rising by approximately 3 °C in winter, nearly one degree more than daily maximum temperatures during the same season. Annually averaged diurnal temperature range has generally decreased in Finland from 1961–1990 to 1991–2020. The decrease in DTR was statistically significant in the northern part of Finland, and overall, the country experienced a statistically significant decrease of −0.25 °C. The decreases in annual mean DTR exhibited a latitudinal pattern, with the largest decrease observed in northern Finland and smallest in southern Finland. The majority of the decrease in DTR occurred during winter across the country, whereas changes in the other seasons were smaller and varied in direction. A decrease in DTR in Finland has been reported by other studies, although the results in this thesis (−0.09 °C/decade trend) are larger in amplitude compared to other estimates. The decrease in winter DTR was attempted ...